1986
DOI: 10.1093/nar/14.12.5013
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of ionizing radiation–induced mutagenesis in thelacregion of single–stranded phage M13 mp10 DNA

Abstract: M13 mplO single-stranded phage DNA was irradiated-with Co gamma-rays, and transfected into Escherichia coli. One hundred and sixteen mutant clones having lesions in the lac insert were selected, and mutational sites w-ere examined by DNA sequence analysis. Fourteen out of the 15 nucleotide changes thus detected were base substitutions, and the rest was a base addition. Transitions and transversions were almost equal in number. Mutational events were observed at cytosine residues more frequently than at other r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Fin ally, when we com pare our data with those reported by Ayaki et al (1986) on n aked ss M 13m p10 DN A, irradiated in an oxygen ated Tris-ED TA buffer solution, there seem to be m any sim ilarities, like predom inant C ® T tran sitions (47% in their paper com pared to 48% in th is paper, Table 2) and a n on -random distribution of the m utations, being con centrated for an im portant part in certain regions or positions. From this com parison it m ay be derived, th at the direct effect plays only a m inor role w hen bacteriophages are irradiated in N B or otherwise that the D N A dam age pattern caused by th e direct effect is rough ly th e sam e as that by th e indirect effect.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Fin ally, when we com pare our data with those reported by Ayaki et al (1986) on n aked ss M 13m p10 DN A, irradiated in an oxygen ated Tris-ED TA buffer solution, there seem to be m any sim ilarities, like predom inant C ® T tran sitions (47% in their paper com pared to 48% in th is paper, Table 2) and a n on -random distribution of the m utations, being con centrated for an im portant part in certain regions or positions. From this com parison it m ay be derived, th at the direct effect plays only a m inor role w hen bacteriophages are irradiated in N B or otherwise that the D N A dam age pattern caused by th e direct effect is rough ly th e sam e as that by th e indirect effect.…”
Section: Discussionsupporting
confidence: 62%
“…Also in this case no m utations appeared to be form ed on A/T base pairs. In fact, in all studies perform ed sofar, in wh ich ss or ds D N A was irradiated in aqueous solution a very high preferen ce for point m utation s on G /C base pairs was observed irrespective, wh eth er the irradiated D NA was allowed to replicate in E. coli or m am m alian cells (Ayaki et al 1986, Tindall et al 1988, Takim oto et al 1991, Sikpi et al 1991, Waters et al 1991, Bertram and H agen, 1992.…”
Section: Discussionmentioning
confidence: 99%
“…The major stable product of thymine modification in vitro and in vivo is 5,6-dihydroxy-5,6-dihydrothymine (thymine glycol or t'; predominantly the cis isomers) (7,8). Several studies have shown that t' inhibits DNA synthesis in vitro in most sequences (9-12), although certain local contexts allow DNA polymerases to bypass the lesion (12).The mutational specificity of ionizing radiation has been studied in bacteria and in mammalian cells (13)(14)(15)(16)(17)(18)(19). Base substitutions are the most frequently detected mutational event and, although there is no specificity for any one substitution, most studies agree that the major mutational change is the G-C A-T transition.…”
mentioning
confidence: 99%
“…The mutational specificity of ionizing radiation has been studied in bacteria and in mammalian cells (13)(14)(15)(16)(17)(18)(19). Base substitutions are the most frequently detected mutational event and, although there is no specificity for any one substitution, most studies agree that the major mutational change is the G-C A-T transition.…”
mentioning
confidence: 99%
“…The basepairing capability of altered cytosines has not been examined. However, mutations of cytosine loci were observed by DNA sequence analysis following recovery of mutant M13 bacteriophage DNA after treatment with ionizing radiation [21]. Furthermore, the predominant site of mutations in Os04-oxidized DNA was demonstrated to be at cytosines rather than thymines [20].…”
Section: Resultsmentioning
confidence: 99%